A Flat Circle? Recurrences and Differences in Memories of the Last Dictatorship during the Rise of Argentina’s Radical Right - Salvi, Valentina; Grinchpun, Matías (Hispania Nova, 2026)
Javier Milei’s victory in the 2023 presidential election challenged the established consensus that had prevailed since the democratic transition in several ways, for example by officialising what until then had been a counter-memory of the last military dictatorship. This paper takes as a star ting point a set of meanings of terms reclaimed by the libertarian discursive formation to refer to the 1970s, such as “war”, “terrorism”, “there were not 30,000” and “curro (theft) of human rights”, and aims to rebuild the layers of meaning that overlap in this configuration of memory by considering its historical lineage. On the one hand, following Foucauldian notions of origin and emergence, it analyses the course of historical and political events which contributed a plexus of meanings from the years before the coup up to the present. On the other hand, it examines the growing tensions and disagreements that contributed to the pervasiveness, dissemination or obliteration of such meanings in the public debate.